Measuring employee performance - Hutchinson, Sue (Henry Stewart Talks, 2019)
Employee performance, First line management, Setting objectives, Monitoring performance, feedback, Professional development, Key performance indicators, Output-based approach, Behavioural approach, SMART objectives, Performance management